2023
DOI: 10.3390/jcs7040133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 and SiC Nano-Fillers on the Mechanical Properties of Carbon Fiber-Reinforced Epoxy Hybrid Composites

Abstract: Polymeric nanocomposites are an emerging research topic, as they improve fiber-reinforced composites’ thermo-mechanical and tribological properties. Nanomaterials improve electrical and thermal conductivity and provide excellent wear and friction resistance to the polymer matrix material. In this research work, a systematic study was carried out to examine the tensile and hardness properties of a carbon fiber epoxy composite comprising nano-sized Al2O3 and SiC fillers. The study confirms that adding nano-fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…From the earlier work of the authors, it was proven that an optimal quantity of 1.75 wt% Al 2 O 3 and 1.25 wt% SiC nanofiller added to CFRP composites enhances interlaminar shear strength, tensile strength, toughness, and flexural resistance as compared to a neat CFRP composite. This further showcases that the addition of nanofiller to the matrix decreases stiffness between laminas, resulting in lower delamination [4,5]. The minimum F d value was obtained for the 4 mm drill diameter, higher spindle speed (5500 rpm), and lower feed (0.01 mm rev -1 ).…”
Section: Delamination Analysissupporting
confidence: 54%
See 2 more Smart Citations
“…From the earlier work of the authors, it was proven that an optimal quantity of 1.75 wt% Al 2 O 3 and 1.25 wt% SiC nanofiller added to CFRP composites enhances interlaminar shear strength, tensile strength, toughness, and flexural resistance as compared to a neat CFRP composite. This further showcases that the addition of nanofiller to the matrix decreases stiffness between laminas, resulting in lower delamination [4,5]. The minimum F d value was obtained for the 4 mm drill diameter, higher spindle speed (5500 rpm), and lower feed (0.01 mm rev -1 ).…”
Section: Delamination Analysissupporting
confidence: 54%
“…Recently, various inorganic fillers have been used by researchers to improve the performance of these composites. Some of the inorganic fillers are as follows: aluminum oxide (Al 2 O 3 ), silicon carbide (SiC), silicon Oxide (SiO 2 ), titanium dioxide (TiO 2 ), and calcium carbonate (CaCO 3 ) [4][5][6][7]. The inorganic fillers added are either micro or nano-sized particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While analyzing the effects of filler ratios on tensile strength in Figure 9B, it can be observed that increases are achieved for all filler ratios compared to the unfilled condition. The reason for fillers enhancing the tensile strength of the composite is attributed to the good wetting of the matrix by the filler particles and the strong bonding between the oxygen in the fillers and the polymer, which increases the load‐carrying capacity 29 . However, it is determined that there is not a linear relationship between filler ratios and tensile strength.…”
Section: Resultsmentioning
confidence: 99%
“…The biooil/DGEBA/biochar mixture and curing agent were homogeneously mixed in 1:0.1 weight proportions and then stirred for 10 min until a complete dispersion of biochar was reached. The dispersion of biochar is challenging due to the dense nature of the epoxy resin because increasing the weight fraction of biochar in epoxy increases the viscosity of epoxy [31]. Subsequently, blends were degassed in a vacuum desiccator attached to a vacuum pump to remove the entrapped air, poured into a silicone mold, cured at 50 • C for 8 h, postcured at 65 • C for 12 h in an oven (Memmert UF-260 universal), and stored at room temperature.…”
Section: Preparation Of Bio-based Epoxy Blendsmentioning
confidence: 99%